1999
DOI: 10.1001/archinte.159.13.1437
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hospital-Acquired Staphylococcus aureus Bacteremia

Abstract: The presence of a central venous catheter is an important risk factor, and hyponatremia and anemia are associated with the development of hospital-acquired SAB. Furthermore, hospital-acquired SAB in itself increases mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(76 citation statements)
references
References 76 publications
4
66
1
1
Order By: Relevance
“…The mortality-rate ratio for cancer was 1.7 (95%CI:0.8-3.5). However, this was not significantly (p = 0.14) different from baseline mortality [12].…”
Section: The Studiesmentioning
confidence: 57%
“…The mortality-rate ratio for cancer was 1.7 (95%CI:0.8-3.5). However, this was not significantly (p = 0.14) different from baseline mortality [12].…”
Section: The Studiesmentioning
confidence: 57%
“…The search revealed nine publications that reported differences between men and women with respect to incidence of BSI (Table 5, available online). [23][24][25][26][27][28][29][30][31] Controlling for a variety of covariates, three of the articles reported that men had significantly higher infection rates than women, and six reported no significant gender differences. Although the majority found no significant gender differences, the fact that all studies reporting significant differences found that males were at higher risk suggests a possible association.…”
Section: Discussionmentioning
confidence: 99%
“…Por exemplo, os ECoN são bactérias que colonizam a pele, fossas nasais e orofaringe dos humanos, sendo consideradas bactérias oportunistas de grande importância dentro de hospitais, principalmente pela sua capacidade de colonizar cateteres e sondas (Deighton & Beverley 1990, Stratton 2000, Arciola et al 2001. Staphylococcus aureus pode ser encontrado como parte da fl ora normal ou transitória do homem, sendo considerado um dos principais patógenos relacionados com infecções nosocomiais (Jensen et al 1999, Almeida et al 2007.…”
Section: Discussionunclassified